STRATEGI OPTIMALISASI KLAIM JAMINAN KESEHATAN NASIONAL DI UNIT CASEMIX RUMAH SAKIT “X” BLITAR - Syahira, Nurfathina; Rusdi, Achmad Jaelani; Akbar, Prima Soultoni (UI Scholars Hub, 2024)
The funding for patient care of participants of the Social Security Administering Body (BPJS) Health in hospitals is carried out through a claim mechanism. This study aims to design a strategy to optimize the claims for patient care costs for BPJS participants at Hospital